Analisis Pengaruh Corporate Governance terhadap Pengungkapan Islamic Social Responsibility Disclosure - Della Putri Apriliana (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This study aims to analyze the effect of corporate governance on the disclosure of Islamic Social Responsibility (ISR). With a quantitative approach, the hypothesis of this study was tested by linear regression analysis. With a purposive sampling technique, three Islamic commercial banks were selected as the research subjects. The results of this study indicate that the size of the board of commissioners and concurrent positions of the board of commissioners do not affect the disclosure of Islamic Social Responsibility (ISR).Keywords: Islamic Social Responsibility (ISR), commissioner board, corporate governance